Dietary overlap in spiny dogfish (Squalus acanthias) and thornback ray (Raja clavata) in the southeastern Black Sea - Demirhan, Sefa Ayhan; Seyhan, Kadir; Basusta, Nuri (Foundation Environmental Protection & Research-Fepr, 2007)
The food composition and dietary overlap between the spiny dogfish (Squalus acanthias) and thornback ray (Raja clavata) were studied in the Eastern Black Sea. It was found that the food of S. acanthias and R. clavata in the area studied consisted of mainly fish and crustaceans. The availability of prey was found to be the main criterion in the spiny dogfish feeding strategy. In winter, anchovy were the dominant prey for S. acanthias. This reflects that there is a high availability of these prey in the region. The availability of prey items affected the diet composition, the values of diet breadth, the prey similarity and the dietary overlap of the thornback ray and spiny dogfish. The study has shown that the prey similarity index of these species was 38%. The diet of R. clavata was significantly overlapped by the diet of S. acanthias (1.38). However, S. acanthias was observed to have a more unique diet and was insignificantly overlapped by R. clavata (0.36). The overall results indicate that the spiny dogfish is an indiscriminate predator preying upon those species that are most abundant and available in the area and season, and that R. clavata also feed mainly on anchovy and whiting in the winter but shift to crab and Gobius sp., a demersal species common in the area, together with whiting for the rest of the year.
Keywords: Black Sea; dietary overlap; food composition; Raja clavata; Squalus acanthias